FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA HUBUNGAN PEMASOK DAN PEMBELI SERTA DAMPAKNYA TERHADAP KEUNGGULAN BERSAING PADA BISNIS SKALA MIKRO PENYEDIA MAKANAN DAN MINUMAN DI KAWASAN UNDIP TEMBALANG - Pramudita, Anitya Pinasthika; Dwiyanto, Bambang Munas (Faculty of Economics and Business Diponegoro University, 2017)
Food and beverage business provider wide-spread in the city of Semarang. Judging from the quantity, micro businesses in the fields of food and beverage provider has more significant numbers when compared to businesses with large scale or the middle scale. However, development of micro-businesses still has many obstacles such as lack of fund, low levels of human resources and lack of awareness to build good relationships towards suppliers, whereas the supplier holds important role in business success. Added with the large number of existing business competitors, it requiresdomination to compete of each business in order to survive in the existing competitive conditions. This research’s objectives are to test the influence of information sharing, long term relationship and process integration against the competitive advantage of food and beverage business in UNDIP Tembalang with supplier and buyer relationship performance as intervenning.Taking a sample of 100 respondents with simple random sampling technique selecting respondents who are micro business of food and beverage provider around UNDIP, Tembalang. The method of data analysis used is multiple regression analysis, where the analysis consists of: validity test, reliability test, classical assumption test, multiple linear regression test, t test, F test, determination test and Sobel test.The result of multiple regression shows that the variable of information sharing (0,546), long term relationship (0,304) and process integration (0,136) have positive and significant influence to intervenning variable that is supplier and buyer relationship performance. On the other hand, supplier and buyer relationship performance has positive and significant influence (0,770) with dependent variable that is competitive advantage.